Pemberdayaan Ekonomi Anggota Koperasi Jasa Keuangan Syariah Melalui Produk Pembiayaan di Koperasi Simpan Pinjam dan Pembiayaan Syariah Muamalah Berkah Sejahtera Surabaya - Ardian Dwi Bagus S; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2017)
The cooperation of sharia microfinance institutions that have a role and function of the build and develop potential and economic ability members in particular and the society in general to improve the economic and social welfare. The aim of this research is to find out the role of cooperation sharia financial services in economic empowerment of its members. The approach that is used is qualitative approach by case study as a strategy. In the technique of data collection using the techniques of interview directly to the related objects. This research indicated that the cooperative savings and financing sharia convenient Muamalah Berkah Sejahtera Surabaya has a role in the economic empowerment members through financial products by offering the financing products, with various desired model by its members and the most important thing is that these products are using the contract according to the Islamic Law.